(untitled) (Medical Forum Monthly, 2022)
Objective: To determine the incidence and presentation of ectopic pregnancy presented at Gynecology Unit 1, Civil Hospital Quetta. Study Design: Descriptive study Place and Duration of Study: This study was conducted at the at the Department of Obstetrics and Gynecology, Civil Hospital Quetta for a period of one year from January, 2019 to December, 2019. Materials and Methods: A total of 24 patients with ectopic pregnancy were reported during this time period. All 24 patients were informed and included in the study with their willful consent to participate. Results: Patients had a mean standard deviation age of 29 ± 5.12 years. The youngest patient in the group being of age 22, and the eldest included was of age 38. Out of these 24 patients, 23 (95.8%) were ruptured ectopic while one (4.2%) was unruptured. 10 patients (41.7%) had right sided ectopic pregnancy and 14 patients (58.3%) had left sided ectopic pregnancy. All 24 patients were presented with vaginal bleeding, pelvic pain, abdominal pain, and amenorrhea. Out of these, 14 were also presented with shock. Conclusion: Considering the risk factors and clinical presentation, early diagnosis of ectopic pregnancy can help reduce the mortality and morbidity rate.